Pengaruh TikTok terhadap Minat Membeli Eat Sambel pada Gen Z di Jakarta - Lie, Darren; Junaidi, Ahmad (Kiwari, 2025)
This study was conducted to determine the effect of TikTok on the interest in buying Eat Sambel products among Gen Z in Jakarta. TikTok, as a short video social media, has become an effective promotional platform for Eat Sambel, a micro, small and medium-sized culinary business that offers various variants of the archipelago's signature chilli sauce. This research uses a quantitative method with purposive sampling technique. The survey was distributed to 100 respondents who are TikTok users and belong to Gen Z in Jakarta. Data was collected through an online questionnaire that was processed using SPSS. The results showed that TikTok has a positive and significant influence on the interest in buying Eat Sambel products, with a contribution of 60.2% to the purchase intention variable. Key features such as TikTok Shop and live streaming are important factors in creating interactive experiences and increasing consumer appeal. Creative content, such as recipe videos and customer reviews, also contribute to building purchase intention. This research underscores the importance of using social media, especially TikTok, as an effective digital marketing tool to reach young consumers. The findings provide strategic guidance for businesses to optimise the use of TikTok to increase brand awareness and attract purchase intention of consumers, especially Gen Z in the digital era. Penelitian ini dilakukan untuk mengetahui pengaruh TikTok terhadap minat membeli produk Eat Sambel di kalangan Gen Z di Jakarta. TikTok, sebagai media sosial video singkat telah menjadi wadah promosi yang efektif bagi Eat Sambel, sebuah usaha mikro kecil dan menengah bidang kuliner yang menawarkan berbagai varian sambal khas Nusantara. Penelitian ini menggunakan metode kuantitatif dengan teknik purposive sampling. Survei disebarkan pada 100 responden pengguna TikTok dan termasuk dalam Gen Z di Jakarta. Data dikumpulkan melalui kuesioner online yang diolah menggunakan SPSS. Hasil dari penelitian menunjukkan bahwa TikTok memiliki pengaruh positif dan signifikan terhadap minat membeli produk Eat Sambel, dengan kontribusi sebesar 60,2% terhadap variabel minat beli. Fitur utama seperti TikTok Shop dan live streaming menjadi faktor penting dalam menciptakan pengalaman interaktif dan meningkatkan daya tarik konsumen. Konten kreatif, seperti video resep dan ulasan pelanggan, juga berkontribusi dalam membangun minat beli. Penelitian ini menggarisbawahi pentingnya penggunaan media sosial, terutama TikTok, sebagai alat pemasaran digital yang efektif untuk menjangkau konsumen muda. Temuan ini memberikan panduan strategis bagi pelaku usaha untuk mengoptimalkan penggunaan TikTok dalam meningkatkan kesadaran merek dan menarik minat beli konsumen, khususnya Gen Z di era digital.